El fracaso de la construcción nacional en una ciudad de provincias. La conmemoración del Greco (1914) en Toledo - Eric Storm (Mélanges de la Casa de Velázquez, 2012)
An analysis of the El Greco commemoration held in 1914 shows that the process of national construction encountered numerous obstacles in a provincial town like Toledo. Before even starting, it was very difficult to agree about its organisation, partly because the elite circles of Toledo were antagonistic to the tutelage of Madrid. In the end, the centenary was a small-scale event and its organisation was dominated by the conservative authorities, the Church and the royal academies. While almost all the local newspapers wished to make the event a success, only the weekly published by the liberal-democrats and the republicans sought to use the commemoration to stimulate national sentiment in the population. National-catholicism, which acquired considerable importance later on, was not in evidence, for the Catholic right put the interests of the Church before those of the nation or even of the town. Consequently, instead of promoting national unity among the local population, the third centenary of the painter’s death prompted an exchange of insults between the Catholic right and the anticlerical left.